80-211 Spring 2003
Due on Friday, April 4th
Note: This assignment is divided into two sections; the first section has some problems on material covered since the last assignment and the second section, which is a review meant to help you study for the exam. The first section will be graded as usual, where as the second section you will receive all 4 points if you make a reasonable effort to do all the problems. You won?t be able to redo the second section.
Section 1 (6 pts):
Problem 1: Show that the sentences below are not semantically equivalent. Give a brief explanation why.
$xFx & $xGx, $x(Fx & Gx)
Problem 2: Establish that the following sequents are invalid by constructing an appropriate interpretation. Give a brief explanation why as above.
(a) "x(Fx→Gx), "x(Hx→Gx) ├ "xGx
(a) "x(Bx→Cx), $xBx ├ "xCx
(b) "x$yRxy ├ "x"yRxy
Problem 3: Read in the text pages 159-167. Do problem 1(e) and 3(a) on page 168 of your text.
Section 2 (4 pts):
Problem 1: Define what it means to be semantically true and semantically false in predicate logic. Also state what it means for two sentences to be semantically equivalent.
Problem 2: Do problems (p), (o), (t), (w) on page 103 of your text.
Problem 3: Prove the following sequents using the four quantifier rules and primitive or derived rules of the propositional calculus.
(a) "x(Fx ↔ Gx) ├ "xFx ↔ "xGx
(b) "x(Fx→~Gx) ├ ~$x(Fx & Gx)
(c) "x(Fx v Hx→Gx & Kx), ~"x(Kx & Gx) ├ $x~Hx
(d) "x(~Gx v ~Hx), "x((Jx→Fx)→Hx) ├ ~$x(Fx & Gx)
(e) "x($yFyx→"zFxz) ├ "y"x(Fyx→Fxy)
Problem 4: Prove the following sequents using the any primitive or derived rules for propositional/predicate logic.
(a) "x(Fx→Gx) ├ $xFx→$xGx
(b) "xFx → "xGx ├ $x(Fx → Gx)
(c) ├ ~"x(Fx↔Gx) v ($xFx ↔ $xGx)